Freedom and Indigenous constitutionalism - Borrows, John (University of Toronto Press, 2016)
"Indigenous traditions can be uplifting, positive, and liberating forces when they are connected to living systems of thought and practice. Problems arise when they are treated as timeless models of unchanging truth that require unwavering deference and unquestioning obedience. Freedom and Indigenous Constitutionalism celebrates the emancipatory potential of Indigenous traditions, considers their value as the basis for good laws and good lives, and critiques the failure of Canadian constitutional traditions to recognize their significance."-- Provided by publisher., "Demonstrating how Canada's constitutional structures marginalize Indigenous peoples' ability to exercise power in the real world, John Borrows uses Ojibwe law, stories, and principles to suggest alternative ways in which Indigenous peoples can work to enhance freedom. Among the stimulating issues he approaches are the democratic potential of civil disobedience, the hazards of applying originalism rather than living tree jurisprudence in the interpretation of Aboriginal and treaty rights, American legislative actions that could also animate Indigenous self-determination in Canada, and the opportunity for Indigenous governmental action to address violence against women."-- Provided by publisher.